Heavy Metals Tolerant Bacteria Detection from Selected Scrap Metal Dump Site: A Review - Muhammad, Haladu Mahmud; Nasir, Mukhtar Umar; Adam, Ansar Bilyaminu; Shamsuddeen, Ruslan (Darul Yasin Al Sys, 2024)
This study aimed to detect heavy-tolerant bacteria from selected scrap metal dump sites. Heavy metals are the major setbacks to many forms of life and their presence in the ecosystem rapid increase of heavy metal contamination is due to anthropogenic activities, rampant scrap metal waste disposal, and other industrial wastes. Bacteria were found to be among the many microorganisms that can tolerate many heavy metals and can as well reduce their toxicity or even convert them to useful resources. This study aims to detect the heavy metal concentration and the bacterial species capable of tolerating the identified heavy metals from selected metal dump sites. The heavy metals content of the soil samples was analyzed using Atomic Absorption Spectrophotometry (AAS). Standard methods of enrichment culture and colony count were used to isolate a total of 12 bacterial species. Using 16S rRNA gene sequence-based molecular systematics, the 12 isolates were identified and grouped into one genus (Bacillus). It was observed from the results that the heavy metals (Pb, Zn, Cu, Cd, and Cr) concentrations found to be high above the WHO permissible limits (Copper-2.0, Zinc-3.0, Lead-0.4, Chromium-0.05, and Cadmium-0.03). Therefore, the bacterial isolates capable of surviving at such levels of heavy metals could have a potential application in the bioremediation and bioleaching of heavy metal contaminants.